Visual Outcome after Treatment with High Dose Intravenous Methylprednisolone in Indirect Traumatic Optic Neuropathy - Pokharel, S; Sherpa, D; Shrestha, R; Shakya, K; Shrestha, R; Malla, O K; Pradhananga, C L; Pokhrel, R P; Shrestha, P (Journal of Nepal Health Research Council, 2016)
Background: Traumatic optic neuropathy is an acute injury of the optic nerve due to trauma. It is an ocular emergency, requiring early treatment though there is no proven standard treatment protocol for the condition. Various studies have shown improvement in vision after intravenous steroids, but not statistically significant. Studies have revealed even optical decompression surgery is not the ultimate treatment because of no significant improvement of vision. Our study aims to assess visual outcome after high dose (1 gram) of intravenous methylprednisolone in cases with indirect optic neuropathy. Methods: This was a non-randomized interventional study carried out in Kathmandu Medical College Teaching Hospital from May 1st 2013- June 1st 2014. Results: There were 10 cases with indirect traumatic optic neuropathy included in the study. Four cases received IV methylprednisolone and six cases were observed without steroid treatment. Traumatic optic neuropathy was observed more in males[8 (80%)]with higher number in age group 21-30 years old. The visual recovery after intravenous steroid treatment was rapid and beneficial in cases with vision better than Non Perception of Light (NPL), even in cases presented 4 days after the trauma. Conclusions: There was rapid and beneficial improvement in visual acuity after high dose of intravenous steroid treatment in cases with indirect traumatic optic neuropathy with vision better than Non Perception of Light (NPL). Keywords: Intravenous, methylprednisolone, traumatic optic neuropathy, visual acuity.